Peningkatan Hasil Belajar Siswa Kelas V SDN 28 Karang Pauh Dengan Media Audio Visual Kecamatan Bayang - Indra Saputra (LPPI Yayasan Almahmudi bin Dahlan, 2024)
This study aims to improve the learning outcomes of grade V students of SDN 28 Karang Pauh through the use of audio-visual media. Learning media based on audio visual can help students understand the material more effectively, because it can stimulate the senses of sight and hearing at once. The method used in this research is classroom action research (PTK) carried out in two cycles, with each cycle consisting of planning, implementation, observation, and reflection. The subjects of this research were class V students of SDN 28 Karang Pauh, totaling 14 people. The results showed a significant increase in student learning outcomes after the application of audio-visual media. In cycle I, the average student score was 70, with a percentage of completeness of 60%. In cycle II, the average student score increased to 85, with the percentage of completeness reaching 90%. This shows that the use of audio-visual media can increase students' motivation, understanding, and involvement in the learning process. Based on the results of this study, it can be concluded that the use of audio-visual media can improve the learning outcomes of grade V students of SDN 28 Karang Pauh. Therefore, it is recommended that teachers utilize audio visual media as an alternative in learning to improve the quality of education in elementary schools.